Koexistenz im Ineinander Eine problemgeschichtliche Analyse der Fremdwahrnehmungstheorie und der Intersubjektivitätsproblematik im Denken Edmund Husserls - Sandu, Paul Gabriel (Mohr Siebeck, 2021)
The question of intersubjectivity, which constitutes the main topic of this work, is one of the most intricate problems of Husserls transcendental phenomenology. In order to deal with this problem, the author combines a historical approach with a systematic approach, thus opening up a new perspective on the matter.
PublicationDate: 20210217
Keywords: Leiblichkeit -- Privilegierung -- Fremdwahrnehmung -- Sozialzwecknormen -- Einfühlung -- Konvaleszenz -- Geschichte der Neutestamentlichen Wissenschaft -- transzendentale Intersubjektivität -- C. F. Georg Heinrici -- Cartesianismus -- urtümliches Strömen -- Personhood -- Hermeneutik -- Phänomenologie